The role of muscle-specific MicroRNAs in patients with chronic obstructive pulmonary disease and skeletal muscle dysfunction - Zhao, Hui; Li, Peijun; Wang, Jihong (Frontiers in Physiology, 2022)
Skeletal muscle dysfunction is a systemic manifestation of chronic obstructive pulmonary disease (COPD), manifested through the changes in the respiratory and peripheral muscle fibre types, reducing muscle strength and endurance, and muscle atrophy. Muscle dysfunction limits the daily mobility, reducing the quality of life, and may increase a patient's risk of mortality. MicroRNAs (miRNAs) as the regulators of gene expression, plays an important role in modulating skeletal muscle dysfunction in COPD by regulating their skeletal muscle development (proliferation, differentiation), protein synthesis and degradation, inflammatory response and metabolism, and in particular, muscle-specific miRNAs (myomiRs) may play an important role. However, the different expressions of myomiRs in COPD and skeletal muscle dysfunction and the mechanisms underlying their role remain unclear. Therefore, this paper reviews the differential expression of the myomiRs in COPD to identify myomiRs that play a role in skeletal muscle dysfunction in COPD and further explore their possible mechanisms and action in order to provide new ideas for the prevention and treatment of the skeletal muscle dysfunction in COPD.